Risk factors for sudden death in athletes, is there a role for screening? - Hajduczok, A. G.; Ruge, M.; Emery, M. S. (Current Cardiovascular Risk Reports, 2022)
Purpose of Review: Sudden cardiac death (SCD) in a young athlete is an infrequent yet devastating event often associated with substantial media attention. Screening athletes for conditions associated with SCD is a controversial topic with debate surrounding virtually each component including the ideal subject, method, and performer/interpreter of such screens. In fact, major medical societies such as the American College of Cardiology/American Heart Association and the European Society of Cardiology have discrepant recommendations on the matter, and major sporting associations have enacted a wide range of screening policies, highlighting the confusion on this subject. This review seeks to summarize the literature in this area to address the complex and disputed subject of screening young athletes for SCD. Recent Findings: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can cause myocarditis, which is one acquired cardiac disease associated with SCD. The coronavirus 2019 (COVID-19) pandemic has therefore resulted in an increased incidence of an otherwise less common condition, providing an expanded dataset for further study of this condition. Recent findings indicate that cardiac complications of athletes with myocardial involvement of SARS-CoV-2 infection are rare. Other contemporary work in SCD screening has been focused on the implementation of various screening protocols and measuring their effectiveness. Summary: No universal consensus exists for athlete screening for conditions associated with SCD with varying guidelines and protocols across cardiology and sport-specific organizations. No screening program will prevent all SCD; however, small programs managed by physicians familiar with the examination of an athlete that carefully personalize screening to the individual may maximize detection of dangerous cardiac conditions while minimizing false positives.